Feasibility of training practice nurses to deliver a psychosocial intervention within a collaborative care framework for people with depression and long-term conditions. Issue 1 (December 2016) - Webster, Lisa; Ekers, David; Chew-Graham, Carolyn
Abstract Background Practice nurses (PNs) deliver much of the chronic disease management in primary care and have been highlighted as appropriately placed within the service to manage patients with long-term physical conditions (LTCs) and co-morbid depression. This nested qualitative evaluation within a service development pilot provided the opportunity to examine the acceptability of a Brief Behavioural Activation (BBA) intervention within a collaborative care framework. Barriers and facilitators to engaging with the intervention from the patient and clinician perspective will be used to guide future service development and research. Methods The study was conducted across 8 practices in one Primary Care Trust1 in England. Through purposive sampling professionals (n  = 10) taking part in the intervention (nurses, GPs and a mental health gateway worker) and patients (n  = 4) receiving the intervention participated in semi-structured qualitative interviews. Analysis utilised the four Normalisation Process Theory (NPT) concepts of coherence, cognitive participation, collective action and reflexive monitoring to explore the how this intervention could be implemented in practice. Results Awareness of depression and the stigma associated with the label of depression meant that, from a patient perspective a PN being available to 'listen' was perceived as valuable. Competing practice priorities, perceived lack of time and resources, and lack of engagement by the whole practice team were considered the greatest barriers to the implementation of this intervention in routine primary care. Conclusion Lack of understanding of, participation in, and support from the whole practice team in the collaborative care model exacerbated the pressures perceived by PNs. The need for formal supervision of PNs to enable them to undertake the role of case manager for patients with depression and long-term conditions is emphasised.